0696 The Application of a QTc Risk Score in Patients with Obstructive Sleep Apnea. (25th May 2022) - Patel, Salma; Zareba, Wojciech; Parthasarathy, Sairam; Perez, Karolina; Wendel, Chris; Xia, Xiaojuan; Patel, Imran; Quan, Stuart; Grandner, Michael; Youngstedt, Shawn; Miller, Jerod; Woosley, Raymond
Abstract: Introduction: Evidence suggests that patients with obstructive sleep apnea (OSA) are at risk for QTc prolongation which, is a known risk factor for arrhythmias, sudden cardiac death and all cause mortality. QTc risk scores have been implemented widely to help physicians identify patients at risk for mortality however, these risk scores have not been routinely implemented in patients undergoing sleep studies or those diagnosed with OSA. The goal of this study was to evaluate the distribution of pro-QTc risk scores for patients with and without OSA diagnosed at our facility and its relationship to mortality. Methods: Medical records of all patients undergoing a sleep study at our sleep center from 2/2012 through 8/2020 were analyzed. Patients were identified with or without OSA based on polysomnography or Type III home sleep study. The pro-QTc risk score was calculated with 1 point assigned for: female sex, QT-prolonging diagnoses and conditions, QT-prolonging electrolyte abnormalities, and QT-prolonging medications defined as medications with known and possible risk of torsades de Pointes based on the CredibleMeds website. Mortality was determined if a death date was noted in the electronic medical record. Results: A total of 2, 834 patient records (54% male, age 58 ± 16 years, n=106 dead) were evaluated. A total of 2, 265 patients (age 58 ±15, 54% male, 89 dead) were identified as having OSA and 428 patients (age 54 ± 18, 41% male, 17 dead) did not have OSA. The remaining patients (n=141) had either central sleep apnea or a combination of both obstructive and central sleep apnea. A higher pro-QTc score was associated with greater mortality regardless of presence of OSA (HR 1.3, p<0.0001, 95% CI 1.12 -1.46) after adjusting for age. The association of pro-QTc with mortality was not increased in the moderate or severe OSA groups compared to those without OSA or mild OSA (p=0.36). Conclusion: Increased pro-QTc scores were associated with greater mortality in all patients undergoing sleep studies. OSA status did not affect this association. Support (If Any): American Academy of Sleep Medicine Foundation (203-JF-18), National Institutes of Health (HL126140, 2L30HL154400-023), University of Arizona Health Sciences Career Development Award (5299903), and University of Arizona Faculty Seed Grant (5833261)